The Relationship between Sleep Quality and Fasting Blood Sugar Levels in Diabetes Mellitus Patients - Indah Dewi Nurjanah; Okti Sri Purwanti (GLOBAL HEALTH SCIENCE GROUP, 2026)
Diabetes mellitus is a major health problem with increasing prevalence and complication rates. Blood sugar control is influenced by various factors, one of which is sleep quality, which plays a role in regulating glucose metabolism. This study aims to determine the relationship between sleep quality and fasting blood sugar levels in diabetes mellitus patients. This study is a quantitative study with a correlational design and a cross-sectional approach conducted on 114 type 2 diabetes mellitus patients at the Internal Medicine Polyclinic of Dr. Moewardi Regional General Hospital, Surakarta. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) questionnaire, while fasting blood sugar levels were obtained from patient medical records. Data analysis was carried out descriptively and inferentially using the Chi-Square test. The PSQI questionnaire has been tested for validity and reliability by Fatmawati (2013) using the Pearson product moment correlation coefficient , with a correlation coefficient value (r count) ranging from 0.487–0.778 (r table > 0.444) and a Cronbach's alpha value of 0.63. Most respondents had poor sleep quality (79.8%) and high fasting blood sugar levels (> 126 mg/dL) (82.5%). The chi-square test results showed a significant association between sleep quality and fasting blood sugar levels (p = 0.001). Poor sleep quality was significantly associated with increased fasting blood sugar levels in patients with diabetes mellitus. These findings suggest that sleep quality plays a crucial role in glycemic control, and efforts to improve sleep quality should be considered as part of a comprehensive approach to diabetes mellitus management.